Conformational Dynamics of Herpesviral NEC Proteins in Different Oligomerization States - Diewald, Benedikt; Socher, Eileen; Söldner, Christian; Sticht, Heinrich (International Journal of Molecular Sciences, 2018)
All herpesviruses use a heterodimeric nuclear egress complex (NEC) to transport capsids out of host cell nuclei. Despite their overall similar structure, NECs may differ significantly in sequence between different viruses. Up to now, structural information is limited to isolated NEC heterodimers and to large hexagonal lattices made up of hexagonal ring-like structures (Hexagons). The present study aimed to expand the existing structural knowledge with information on the dynamics of NECs from different viruses and in different oligomerization states. For this task, comparative molecular dynamics simulations were performed of the free NEC heterodimers from three different viruses (HCMV (human cytomegalovirus), HSV-1 (herpes simplex virus 1), and PRV (pseudorabies virus)). In addition, higher oligomerization states comprising two or six NEC heterodimers were characterized for HCMV and HSV-1. The study revealed that the isolated NEC heterodimers from - (HSV-1, PRV) and -herpesviruses (HCMV) differ significantly in their dynamics, which can be attributed to a poorly conserved interface region between the NEC subdomains. These differences become smaller for higher oligomerization states, and both HCMV and HSV-1 individual Hexagons exhibit a common region of enhanced dynamics, which might be of functional relevance for the formation of curved vesicle structures or the recognition of hexameric capsid proteins.
EVALuna2:35491

Properties of Oligomeric Interaction of the Cytomegalovirus Core Nuclear Egress Complex (NEC) and Its Sensitivity to an NEC Inhibitory Small Molecule - Kicuntod, Jintawee; Alkhashrom, Sewar; Häge, Sigrun; Diewald, Benedikt; Müller, Regina; Hahn, Friedrich; Lischka, Peter; Sticht, Heinrich; Eichler, Jutta; Marschall, Manfred (Viruses, 2021)
Herpesviral nuclear egress is a regulated process shared by all family members, ensuring the efficient cytoplasmic release of viral capsids. In the case of human cytomegalovirus (HCMV), the core of the nuclear egress complex (NEC) consists of the pUL50-pUL53 heterodimer that builds hexameric lattices for capsid binding and multicomponent interaction, including NEC-associated host factors. A characteristic feature of NEC interaction is the N-terminal hook structure of pUL53 that binds to an alpha-helical groove of pUL50, thus termed as hook-into-groove interaction. This central regulatory element is essential for viral replication and shows structural-functional conservation, which has been postulated as a next-generation target of antiviral strategies. However, a solid validation of this concept has been missing. In the present study, we focused on the properties of oligomeric HCMV core NEC interaction and the antiviral activity of specifically targeted prototype inhibitors. Our data suggest the following: (i) transiently expressed, variably tagged versions of HCMV NEC proteins exert hook-into-groove complexes, putatively in oligomeric assemblies that are distinguishable from heterodimers, as shown by in vitro assembly and coimmunoprecipitation approaches; (ii) this postulated oligomeric binding pattern was further supported by the use of a pUL50::pUL53 fusion construct also showing a pronounced multi-interaction potency; (iii) using confocal imaging cellular NEC-associated proteins were found partly colocalized with the tagged core NECs; (iv) a small inhibitory molecule, recently identified by an in vitro binding inhibition assay, was likewise active in blocking pUL50-pUL53 oligomeric assembly and in exerting antiviral activity in HCMV-infected fibroblasts. In summary, the findings refine the previous concept of HCMV core NEC formation and nominate this drug-accessible complex as a validated antiviral drug target.
CRIS-Team WoS Importer:2021-04-09

The human cytomegalovirus nuclear egress complex unites multiple functions: Recruitment of effectors, nuclear envelope rearrangement, and docking to nuclear capsids - Marschall, Manfred; Muller, Yves; Diewald, Benedikt; Sticht, Heinrich; Milbradt, Jens (Reviews in Medical Virology, 2017)
Keywords: antiviral drugs; capsid-NEC docking; herpesviruses; human cytomegalovirus; nuclear egress complex